2019
DOI: 10.5902/1980509815187
|View full text |Cite
|
Sign up to set email alerts
|

Estimativa da oferta de biomassa florestal em povoamentos de <i>Pinus taeda</i> L. após intervenções culturais

Abstract: Com a determinação do quanto de biomassa florestal é gerada após as intervenções culturais é possível definir as áreas passíveis de exploração. Com isso, o objetivo do trabalho foi quantificar e estimar a oferta de biomassa de Pinus taeda L. disponível após as intervenções culturais. O experimento foi realizado em reflorestamentos nos municípios dos estados do Paraná e Santa Catarina, com idades de 3 anos (primeira desrama), 5 anos (segunda desrama), 7 anos (terceira desrama), 11 anos (primeiro desbaste) 19 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
2
0
1
Order By: Relevance
“…The Secretariat, in this way, is responsible for urban cleaning such as pruning, weeding and sweeping and its proper destination where it is carried out by professionals trained to perform such action. It is estimated that in 2017, about 47.8 million tons of biomass residues were generated, originating from the forest base, including bark, branches, leaves, chips, sawdust and wood chips that can be reused especially for energy generation (FERREIRA et al, 2019). According to the survey carried out, tree branches were found intertwining the electrical network, as shown in Figure 4.…”
Section: Resultsmentioning
confidence: 99%
“…The Secretariat, in this way, is responsible for urban cleaning such as pruning, weeding and sweeping and its proper destination where it is carried out by professionals trained to perform such action. It is estimated that in 2017, about 47.8 million tons of biomass residues were generated, originating from the forest base, including bark, branches, leaves, chips, sawdust and wood chips that can be reused especially for energy generation (FERREIRA et al, 2019). According to the survey carried out, tree branches were found intertwining the electrical network, as shown in Figure 4.…”
Section: Resultsmentioning
confidence: 99%
“…Conforme Ferreira et al (2019), plantios florestais com maior espaçamento entre as árvores possibilitam maior crescimento em diâmetro, fornecendo madeira do fuste para fins mais nobres e com maior valor agregado. Os valores médios de DAP e altura encontrados neste estudo são semelhantes àqueles observados por Wink (2009), que avaliou o estoque de carbono em Eucalyptus spp.…”
Section: Discussionunclassified
“…For Schikowski et al (2013), the biomass of the other compartments in addition to the stem is extremely important and representative in the total biomass estimation. When quantifying the residue biomass in a Pinus taeda stand after silvicultural interventions, Ferreira et al (2019) indicated the existence of great potential for the exploitation of residue biomass, especially in multiple-use reforestation, with 87.2% of residue remaining in the exploration area referring to the crown (branches and needles).…”
Section: Discussionmentioning
confidence: 99%